Lipopolysaccharide-Activated Bone Marrow-Derived Dendritic Cells Suppress Allergic Airway Inflammation by Ameliorating the Immune Microenvironment - Min, Zhihui; Zeng, Yuzhen; Zhu, Tao; Cui, Bo; Mao, Ruolin; Jin, Meiling; Chen, Zhihong (Frontiers in Immunology, 2021)
Background: Lipopolysaccharide (LPS) produced by Gram-negative bacteria effectively stimulates the maturation of bone marrow (BM)-derived dendritic cells (BMDCs). Previous studies have shown that LPS-activated BMDCs (DClps) might induce tolerance in autoimmune diseases and cancer in vivo, whereas it remains unclear whether DClps can modulate the immune microenvironment in allergic asthma. Objectives: We sought to elucidate the potential effects of DClps on OVA-sensitized/challenged airway inflammation in a mouse model of asthma, which may help facilitate the application of specific tolerogenic dendritic cells (tolDCs) in allergic asthma patients in the future. Methods: We generated and obtained DClps from wild-type mice to evaluate their functional characteristics by ELISA and FACS. We also induced OVA-sensitized/challenged asthmatic mice and intraperitoneally treated these mice with DClps to assess the effects of these injected cells by histopathologic analysis and performing inflammatory cell counts in bronchoalveolar lavage fluid (BALF). Changes in memory CD4+ T cells, regulatory T cells (Tregs) and phosphorylated protein in lung digests were analyzed. Results: DClps exhibited lower levels of CD80 and MHC class II molecules (MHCII) and increased levels of anti-inflammatory cytokines such as IL-10 and TGF-β than immature DCs (DCia). Additionally, DClps treatment dramatically ameliorated airway inflammation and diminished the infiltration of pulmonary inflammatory cells. In addition, we prolonged the modeling time of asthmatic mice and demonstrated that DClps treatment decreased the proliferation activity of pulmonary memory CD4+ T cells, which further rendered the downregulation of type 2 T helper (Th2) cytokines. However, the number of pulmonary Tregs did not discernibly change. DClps treatment also markedly reduced the phosphorylation level of STAT6 protein. Conclusion: Our findings demonstrate that LPS stimulation may lead to a tolerogenic phenotype in BMDCs, which can induce tolerance and regulate the microenvironment of asthmatic mice, possibly through the upregulation of anti-inflammatory cytokines, inhibition of pulmonary memory CD4+ T cells and downregulation of STAT6 phosphorylation.